Aldosterone does not Modify Gene Expression in Human Endothelial Cells - Verhovez, A.; Williams, T. A.; Morello, F.; Monticone, S.; Brizzi, M. F.; Dentelli, P.; Fallo, F.; Fabris, B.; Amenta, F.; Gomez-Sanchez, C.; Veglio, F.; Mulatero, P. (Hormone and Metabolic Research, 2012)
The toxic effects of aldosterone on the vasculature, and in particular on the endothelial layer, have been proposed as having an important role in the cardiovascular pathology observed in mineralocorticoid-excess states. In order to characterize the genomic molecular mechanisms driving the aldosterone-induced endothelial dysfunction, we performed an expression microarray on transcripts obtained from both human umbilical vein endothelial cells and human coronary artery endothelial cells stimulated with 10 − 7 M aldosterone for 18 h. The results were then subjected to qRT-PCR confirmation, also including a group of genes known to be involved in the control of the endothelial function or previously described as regulated by aldosterone. The state of activation of the mineralocorticoid receptor was investigated by means of a luciferase-reporter assay using a plasmid encoding a mineralocorticoid and glucocorticoid-sensitive promoter. Aldosterone did not determine any significant change in gene expression in either cell type both in the microarray and in the qRT-PCR analysis. The luciferase-reporter assay showed no activation of the mineralocorticoid receptor following aldosterone stimulation. The status of nonfunctionality of the mineralocorticoid receptor expressed in cultured human umbilical and coronary artery endothelial cells does not allow aldosterone to modify gene expression and provides evidence against either a beneficial or harmful genomic effect of aldosterone on healthy endothelial cells.
Keywords: mineralocorticoid; endothelial dysfunction; genomic